PENGARUH MULTI-DIMENSI KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJAAKUNTAN PENDIDIK PADA PERGURUAN TINGGI SWASTA DI BANDUNG - Hadijah, Hady Siti (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2012)
Educator Accountant as long one part of from accountant procession owning big enough role indetermining growth of human research in next period and affect growth of accountancy as one sciencearea.One of factor influence thing performance of educator accountant so that can run it profession better issatisfaction in work area. Satisfaction in work area to represent the positive attitude that coming fromjob experience it self.Goals which wish reached in this research are : (1) learning relation of Multidimensional oforganizational commitment developed by Allen and Meyer with the satisfaction work felt by the educatoraccountant, (2) learning influence of Multidimensional of organizational to satisfaction work, (3)learning influence of dimension of affective commitment satisfaction work, (4) learning influence ofdimension of continuance commitment to satisfaction work, (5) learning influence of dimension ofnormative commitment to satisfaction work.Research conducted descriptive and verification while reset method used descriptive survey method byusing technical of with drawls simple random sampling. Institutes which are being research object are13 private sector colleges opening programmed first degree in accountancy and accreditation B by BANPT.gathering technical used is spreading questionnaire. Analyzer used Path Analysis using programmedLisrel 8.30.Results of this research hypothesis examination express: (1) Multidimensional of organizationalcommitment with this satisfaction work is positive correlation and significant, (2) dimension of affectivecommitment have an effect on positive and significant to satisfaction work, (3) dimension of continuancecommitment have an effect on positive and significant to satisfaction work, (4) dimension of normativecommitment don’t have an effect on positive and significant to satisfaction work.